Pathological Laughter as a Symptom of Midbrain Infarction - Ron Dabby; Nathan Watemberg; Yair Lampl; Anda Eilam; Abraham Rapaport; Menachem Sadeh (Behavioural Neurology)
Pathological laughter is an uncommon symptom usually caused by bilateral, diffuse cerebral lesions. It has rarely been reported in association with isolated cerebral lesions. Midbrain involvement causing pathological laughter is extremely unusual. We describe three patients who developed pathological laughter after midbrain and pontine-midbrain infarction. In two patients a small infarction in the left paramedian midbrain was detected, whereas the third one sustained a massive bilateral pontine infarction extending to the midbrain. Laughter heralded stroke by one day in one patient and occurred as a delayed phenomenon three months after stroke in another. Pathological laughter ceased within a few days in two patients and was still present at a two year follow-up in the patient with delayed-onset laughter. Pathological laughter can herald midbrain infarction or follow stroke either shortly after onset of symptoms or as a delayed phenomenon. Furthermore, small unilateral midbrain infarctions can cause this rare complication.